Good girls, good Germans - Askey, Jennifer Drake (Boydell & Brewer, 2013)
The age of nationalism in nineteenth-century Germany generally conjures up images of the Prussian military, Fürst Otto von Bismarck, and Hohenzollern kings who welded together a nation out of disparate principalities through war and domestic social policy. Good Girls, Good Germans looks at how girls and young women became
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Luise; Rhoden; Emmy von; Helm; Clementine; Plehn; Auguste; Der Trotzkopf; Backfischchens Leiden und Freuden; Deutsch; Mädchenliteratur; Geschlechterrolle; Nationalbewusstsein; Mädchenbildung; Lektüre; Nationalismus